Côte d'Ivoire [In West African agriculture and climate change: A comprehensive analysis] - Ahossane, Kadio; Jalloh, Abdulai; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2013)
The West African state of Côte d’Ivoire has an area of 322,465 square kilometers, with a coastline of 540 kilometers along the Gulf of Guinea. It shares borders with Liberia in the southwest, Guinea in the northwest, Mali and Burkina Faso in the north, and Ghana in the east. The southern part of Côte d’Ivoire borders the Atlantic Ocean. In the western part of the coastal areas, there are only two seasons—wet and dry. Moving inland toward the east, a short dry season occurs during the middle of the wet season, creating an annual cycle of four seasons.